2010
DOI: 10.1523/jneurosci.3300-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Sprouting of Adult Nociceptors in Chronic Prostate Cancer-Induced Bone Pain

Abstract: Pain frequently accompanies cancer. What remains unclear is why this pain frequently becomes more severe and difficult to control with disease progression. Here we test the hypothesis that with disease progression, sensory nerve fibers that innervate the tumor-bearing tissue undergo a pathological sprouting and reorganization, which in other non-malignant pathologies has been shown to generate and maintain chronic pain. Injection of canine prostate cancer cells into mouse bone induces a remarkable sprouting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(182 citation statements)
references
References 52 publications
9
169
0
4
Order By: Relevance
“…It must be considered that Inami et al investigated meniscoids excised from participants undergoing laminectomy for cervical myelopathy, removing the dorsal meniscoids at the affected spinal level. Sensory innervation may vary in the presence of pathology, as increased frequency of sensory nerve fibers has been observed in arthritic knee pain [39], breast pain [40], cancer-related pain [41], and non-healed fractures [42], and hypersensitivity of regenerating axonal sprouts is thought to contribute to the perpetuation of symptoms in chronic pain [39,43]. As all participants included in the study of Inami et al had sufficient pain to warrant surgical intervention, and as the neck pain statuses of the cadavers of the present study are unknown, it is plausible that the high nerve fiber frequency reported by Inami et al represents sprouting of sensory nerve fibers in the context of long-standing pain and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It must be considered that Inami et al investigated meniscoids excised from participants undergoing laminectomy for cervical myelopathy, removing the dorsal meniscoids at the affected spinal level. Sensory innervation may vary in the presence of pathology, as increased frequency of sensory nerve fibers has been observed in arthritic knee pain [39], breast pain [40], cancer-related pain [41], and non-healed fractures [42], and hypersensitivity of regenerating axonal sprouts is thought to contribute to the perpetuation of symptoms in chronic pain [39,43]. As all participants included in the study of Inami et al had sufficient pain to warrant surgical intervention, and as the neck pain statuses of the cadavers of the present study are unknown, it is plausible that the high nerve fiber frequency reported by Inami et al represents sprouting of sensory nerve fibers in the context of long-standing pain and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, changes in the expression of neurotransmitters, receptors, ion channels or other phenotypic markers in normal developmental or pathological conditions can also be studied 3,[5][6][7][8][9][10] . Along with appropriate electrophysiological, biochemical and behavioral testing, such changes in peripheral sensory neuron staining patterns can be used to test hypotheses related to various pain states 6,9 , inflammation 11 and neuropathies 5,12 . In conclusion, these techniques provide an invaluable source of in vivo data that complements and reinforces other anatomical, structural and functional data acquired through additional approaches, furthering our understanding of the regulation and acquisition of plasticity in peripheral sensory nerve fibers in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophins could regulate the survival, development, and function of subsets of sensory and sympathetic neurons, and are essential to the generation and maintenance of pain Price et al, 2005). Tyrosine kinase receptor A is detectable in nociceptive sensory nerve fibers innervating the bone, and inhibiting nerve growth factor (NGF) expression could attenuate cancer-induced behavioral signs of pain in BCP mice (Bloom et al, 2011;Halvorson et al, 2005;Jimenez-Andrade et al, 2010;Jimenez-Andrade et al, 2011;Mantyh et al, 2010). Also, treatment against NGF could impact pain-driven peripheral changes in DRG and central changes in the spinal cord .…”
Section: Mechanisms Of Bcpmentioning
confidence: 99%